PEMBUATAN KARBON AKTIF AMPAS KELAPA DENGAN AKTIVATOR ASAM FOSFAT (H3PO4) UNTUK MENGADSORPSI ION LOGAM BESI (Fe) - Prawiranti, Yulizar; Mandasari, Weni; Shofiyah, Sofi S; Febrianty, Irma R; Utami, Naniek T (Akta Kimia Indonesia, 2024)
Peat water contains high iron levels and is reddish-brown in color. Consuming iron in doses above the threshold can endanger health and even lead to sudden death. Additionally, iron pollution can disrupt aquatic ecosystems. Coconut pulp has the potential to adsorb heavy metal iron due to its cellulose, mannan, and galactomannan content. The stages of producing adsorbent from coconut pulp include preparation, carbonization, activation of activated carbon, testing of activated carbon consisting of moisture content, volatile matter content, ash content, and pure carbon content tests, FTIR testing, and determining the % adsorption efficiency of iron (Fe) metal ions and adsorption capacity of iron (Fe) metal ions using Atomic Absorption Spectrophotometry (AAS). Carbonization is carried out at a temperature of 400°C for 2 hours, and activation is performed with 3 N phosphoric acid activator for 24 hours. The FTIR results of coconut pulp activated carbon (CPAC) show a slight increase in the C=O stretching absorption peak and a decrease in almost all absorption peaks such as O-H stretching, C=C aromatic ring, C-H bending, C=O stretching, and =C-H aromatic. A new absorption peak appears in CPAC at the absorption region of 908.47 cm⁻¹, indicating the formation of =C-H aromatic bonds. The efficiency percentage shows that CPAC can adsorb Fe metal ions by 99.16% with an adsorption capacity of 0.22 mg/g, while coconut pulp carbon (CPC) can adsorb Fe metal ions by 34.66% with an adsorption capacity of 0.08 mg/g.